Incidence, risk factors and severity of retinopathy of prematurity in Turkey (TR-ROP study): a prospective, multicentre study in 69 neonatal intensive care units - Bas, Ahmet Yagmur; Demirel, Nihal; Koc, Esin; Isik, Dilek Ulubas; Hirfanoglu, Ibrahim Murat; Tunc, Turan; Hocaoglu, Mumin (Bmj Publishing Group, 2018)
Background To evaluate the prevalence, risk factors and treatment of retinopathy of prematurity (ROP) in Turkey and to establish screening criteria for this condition. Methods A prospective cohort study (TR-ROP) was performed between 1 April 2016 and 30 April 2017 in 69 neonatal intensive care units (NICUs). Infants with a birth weight (BW)=1500 g or gestational age (GA)<= 32 weeks and those with a BW> 1500 g or GA> 32 weeks with an unstable clinical course were included in the study. Predictors for the development of ROP were determined by logistic regression analyses. Results The TR-ROP study included 6115 infants: 4964 (81%) with a GA <= 32 weeks and 1151 (19%) with a GA>32 weeks. Overall, 27% had any stage of ROP and 6.7% had severe ROP. A lower BW, smaller GA, total days on oxygen, late-onset sepsis, frequency of red blood cell transfusions and relative weight gain were identified as independent risk factors for severe ROP in infants with a BW=1500 g. Of all infants, 414 needed treatment and 395 (95.4%) of the treated infants had a BW <= 1500 g. Sixty-six (16%) of the treated infants did not fulfil the Early Treatment for Retinopathy of Prematurity requirements for treatment. Conclusions Screening of infants with a GA <= 34 weeks or a BW<1700 g appears to be appropriate in Turkey. Monitoring standards of neonatal care and conducting quality improvement projects across the country are recommended to improve neonatal outcomes in Turkish NICUs.
Keywords: For-Gestational-Age; Blood-Transfusion; Weight; Infants